Diet composition of the Korean wild boar Sus scrofa coreanus (Suidae) at Mt. Jeombongsan, Korea - Shin, Hyung Min; Kim, Jihee; Jin, Seon Deok; Won, Ho Yeon; Park, Sangkyu (Journal of Ecology and Environment, 2020)
Background: Korean wild boars (Sus scrofa coreanus Heude), because of their adaptability, are a widespread large mammal; however, they sometimes cause problems by invading farms and eating the crops, creating insufficiencies of some foods in South Korea. To understand the diet composition of Korean wild boars according to sex and body size, we collected their feces from Mt. Jeombongsan, Seoraksan National Park, South Korea. The sizes of fecal samples were measured, and genomic DNA was extracted from the samples. We amplified specific loci targeting plants (rbcL and trnL) and animals (COI) to detect the food sources of this omnivore and amplified the ZF and SRY regions to determine the sex. Results: In the wild boar feces, Rosaceae and Bryophyte were the most frequently detected plant food sources at the family level and Diptera and Haplotaxida were the most frequently detected animal food sources at the order level. As a result of sex determination, the sex ratio of wild boars collected in the Mt. Jeombongsan area was approximately 1:1. Our result suggested that there is no significant difference between the diet composition of male and female boars. Based on the average cross-sectional area of the feces, the top 25% were classified into the large body size group and the bottom 25% were classified into the small body size group. The large body size group mainly preferred Actinidiaceae, and the small body size group most frequently consumed Fagaceae. The diet of the large body size group was more diverse than the small body size group. Conclusions: Our results showed that the wild boars preferred Rosaceae, especially Sanguisorba and Filipendula, as plant food sources, and Diptera and Coleoptera of Insecta as animal food sources. Based on the results, the dietary preferences of wild boar appear to be distinguished by not their sex but their body size. Our study could help to elucidate the feeding ecology and population structure of wild boar, as well as address conservation and management issues.
Keywords: Diet; Feces; Mt. Jeombongsan; Sex determination; Sus scrofa